Conditions of journalistic production in political regimes with a highauthoritarian component. The Cuban context - Somohano Fernández, Abel (2025)
The objective is to determine assumptions for studying the conditions of journalistic production in highly authoritarian political regimes. It is argued that there is an explanatory deficiency in the emphasis on the type of political regime when examining the conditions of journalistic production. Therefore, it is necessary to refocus our attention on the multiple dimensions of professional practice, which implies recognizingtransnationalization processes. At the same time, it is stated that the recognition of the explanatory inadequacy in the delimitation of the political regime and the attention to transnationalization processes must be related to the historical concretions of thestructural and normative conditions, extra-media relations, operational-organisational, and individual aspects of journalism. This will lead to an understanding of journalism as a multifaceted practice, resulting from the variable combination of these conditions.The article addresses references in the examination of the conditions of journalistic production in general. It also alludes to the way in which they have been analysed in political regimes with a high authoritarian component, with an emphasis on research based in Cuba. Furthermore, it concludes with a proposal for examining the conditions of journalistic production.